Knowledge and stigma of autism spectrum disorders in Chinese university students in the context of inclusive education - Jinping Hu; Pengwei Fu; Shiying Qiao; Xinai Yan (PLoS ONE, 2025)
This study investigated knowledge of autism spectrum disorder and associated stigma among Chinese university students, utilizing the cross-culturally validated Chinese version of the Autism Stigma and Knowledge Questionnaire. A total of 2,081 students from 25 provinces participated in an online survey. Independent-samples t -tests and one-way ANOVAs revealed that female students, upper-grade students, normal-education students, special education majors, and those who had completed inclusive education courses demonstrated significantly higher levels of ASD knowledge and lower levels of stigma. Prior interactions with autistic people were also associated with greater understanding of ASD and more accepting attitudes. These findings emphasize the significance of incorporating autism-related content into both general and special education curricula, fostering high-quality interactions with autistic communities, and critically considering the types of knowledge that most effectively mitigate stigma. As inclusive education reforms progress in China, enhancing professional training and awareness of neurodiversity will be crucial for preparing future educators to establish inclusive and supportive learning environments.